2008
DOI: 10.1021/jo800524h
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Recyclable Au Nanoparticle-Supported Palladium(II) Interphase Catalysts and Microwave-Assisted Alkyne Cyclotrimerization Reactions in Ionic Liquids

Abstract: The gold nanoparticles with core diameter of 3.9-4.7 nm were stabilized with octanethiolate and dipyridylphosphinicamido undecanethiolate. Without varying the size of central Au cores, palladium complexes were immobilized onto these Au nanoparticles through chelation to the surface-bound dipyridyls. Hybrid catalysts of this type were dissolvable and precipitable, and their structures and reactions were investigated by solution nuclear magnetic resonance (NMR) spectroscopy with a resolution typically attained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 99 publications
1
15
0
Order By: Relevance
“…1-Azidobutane was synthesized in a 80% yield by reaction of 1-bromobutane with NaN 3 in DMSO at 95 °C for 24 h. Likewise, 1-azido-11-undecanethiol was synthesized in 80% overall yield from 1-bromo-11-undecanol (Scheme 2). The NMR data of 1-azidobutane and 1-azido-11-undecanethiol agreed with values reported in the literature 52,53…”
Section: Resultssupporting
confidence: 89%
“…1-Azidobutane was synthesized in a 80% yield by reaction of 1-bromobutane with NaN 3 in DMSO at 95 °C for 24 h. Likewise, 1-azido-11-undecanethiol was synthesized in 80% overall yield from 1-bromo-11-undecanol (Scheme 2). The NMR data of 1-azidobutane and 1-azido-11-undecanethiol agreed with values reported in the literature 52,53…”
Section: Resultssupporting
confidence: 89%
“…The subsequent drop in activity was due to reduction of the cobalt species rather than catalyst leaching, thus, reactivity was restored upon oxidation. A recent study carried out by Yu et al [30] reported a similar activity enhancement for a heterogenized palladium-bipyridyl complex in alkyne cyclotrimerization reactions, which was attributed to interphase effects.…”
Section: Gold Nanoparticles With Mixed Monolayersmentioning
confidence: 69%
“…Cyclotrimerization of alkynes to benzenes was brilliantly achieved using Pd catalyst supported on Au nanoparticles stabilized with thiolates [117]. With a loading of 4 mol % Au-bound Pd(II) catalyst, most of tested alkynes reacted completely in 1 h. The method became appealing when MW Intramolecular Stetter reaction was performed under MW irradiation, either solventless or in ILs, with thiazolium-based ionic liquids that, in turn, were prepared by a one-pot, solvent-free, MW-assisted reaction (Scheme 44) [116].…”
Section: Cyclization Reactions To Carbocycles With C-cbond Formationmentioning
confidence: 99%
“…Cyclotrimerization of alkynes to benzenes was brilliantly achieved using Pd catalyst supported on Au nanoparticles stabilized with thiolates [117]. With a loading of 4 mol % Au-bound Pd(II) catalyst, most of tested alkynes reacted completely in 1 h. The method became appealing when MW Scheme 44.…”
Section: Cyclization Reactions To Carbocycles With C-cbond Formationmentioning
confidence: 99%